Positive electrode active material composite, positive electrode for secondary battery including the same, and secondary battery including the same
The formation of a positive electrode active material composite with a conductive and solid electrolyte coating addresses the conductivity issues in all-solid-state batteries, enhancing performance through improved contact and conductivity.
Patent Information
- Application Number
- JP2023539192
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-07-27
- Filing Date
- 2022-08-01
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2042-08-01
AI Technical Summary
Existing methods for manufacturing electrodes in all-solid-state batteries fail to achieve sufficient close contact between the active material, solid electrolyte, and conductive material, leading to inadequate conductivity and performance issues.
A positive electrode active material composite is formed with a coating layer containing conductive material and solid electrolyte powder, applied through a dry coating process that ensures intimate contact within the pores and on the surface of the active material, enhancing ionic and electrical conductivity.
The composite provides improved ionic and electrical conductivity, resulting in better battery capacity, charge/discharge characteristics, and extended battery life.
Smart Images

Figure 0007614363000003 
Figure 0007614363000001 
Figure 0007614363000002
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0108241 filed on August 17, 2021 and Korean Patent Application No. 10-2022-0092845 filed on July 27, 2022, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to a positive electrode active material composite, a positive electrode for a secondary battery including the same, and a secondary battery including the same. [Background technology]
[0003] In recent years, interest in energy storage technology has been growing. The fields of application have expanded to include energy for mobile phones, camcorders, laptops, and even electric vehicles, and efforts in the research and development of electrochemical elements have become more and more concrete.
[0004] In this respect, electrochemical devices are the field that has attracted the most attention, and among them, the development of rechargeable secondary batteries has been the focus of attention. In recent years, in order to improve the capacity density and non-energy in the development of secondary batteries, research and development into new electrode and battery designs has been actively carried out.
[0005] Among the secondary batteries currently in practical use, lithium-ion batteries are in the spotlight due to their advantages of having a higher operating voltage and a much larger energy density than conventional batteries.
[0006] However, since lithium-ion batteries using liquid electrolytes have a structure in which the negative electrode and the positive electrode are separated by a separator, if the separator is damaged due to deformation or external impact, a short circuit may occur, which may lead to risks such as overheating or explosion.
[0007] In order to solve the above-mentioned problems, solid electrolyte materials using ion-conductive polymers or inorganic substances and all-solid-state batteries using the same are being developed.
[0008] The lithium secondary battery using the solid electrolyte has the advantages of increasing the safety of the battery, preventing leakage of the electrolyte, improving the reliability of the battery, and facilitating the production of a thin battery. Such solid electrolytes can be largely divided into polymer electrolyte materials and inorganic solid electrolyte materials according to the characteristics of the material. The use of solid electrolytes is known to be advantageous from the viewpoint of battery performance such as safety, high energy density, high output, and long life, and is also advantageous from the viewpoints of simplifying the manufacturing process, making the battery larger / more compact, and reducing the cost, and has recently attracted increasing interest.
[0009] Although the lithium ion conductivity of solid electrolytes is still lower than that of liquid electrolytes, it has been reported that theoretically the ion conductivity in solids is higher than that of liquids, and all-solid-state lithium ion batteries are attracting attention from the standpoint of charge / discharge speed and high output.
[0010] When using a solid electrolyte, the active material and the electrolyte must be in intimate contact with each other to ensure ionic conductivity, and therefore a technique is known in which high pressure is applied during electrode fabrication to ensure intimate contact between the active material and the electrolyte.
[0011] However, when simply applying high pressure as in the conventional technology, the high pressure often does not achieve sufficient contact between the active material and the electrolyte, and there is also a risk that the electrode and / or solid electrolyte may be damaged by the application of high pressure, so there is a need to develop a more efficient method.
[0012] On the other hand, when a solid electrolyte is used, not only is there required intimate contact between the active material and the electrolyte, but there is also required intimate contact between the active material and the conductive material.
[0013] However, currently, electrodes for solid-state batteries are mainly manufactured by a method of simply mixing components, and due to limitations in this method, it is difficult to sufficiently reduce the resistance of the electrodes. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] Korean Patent Publication No. 10-2015-0064697 Summary of the Invention [Problem to be solved by the invention]
[0015] The present invention has been devised to solve the above-mentioned problems of the conventional art, and aims to provide a cathode active material composite that can provide excellent ionic conductivity and electrical conductivity by forming an intimate contact structure between a cathode active material and a solid electrolyte and a conductive material, a cathode for a secondary battery including the same, and a secondary battery including the same. [Means for solving the problem]
[0016] In order to achieve the above object, the present invention provides Positive electrode active material; and a coating layer formed on the pores and the surface of the positive electrode active material; The coating layer provides a positive electrode active material composite formed from a coating composition including a conductive material powder and a solid electrolyte powder having a particle size (D50) of 0.3 μm to 2 μm.
[0017] The present invention also provides a positive electrode for a secondary battery, comprising the positive electrode active material composite.
[0018] The present invention also provides a secondary battery comprising the positive electrode, the negative electrode, and a solid electrolyte. Effect of the Invention
[0019] In the cathode active material composite of the present invention, a coating layer is formed on the surface and inside the pores of the cathode active material by the solid electrolyte and the conductive material, and the cathode active material, the solid electrolyte, and the conductive material form a close contact structure, thereby providing excellent ionic conductivity and electrical conductivity.
[0020] In addition, a positive electrode for a secondary battery including the positive electrode active material composite provides excellent ionic conductivity and electrical conductivity.
[0021] In addition, a secondary battery including the positive electrode provides improved battery capacity, charge / discharge characteristics, and life characteristics due to the improved performance of the positive electrode. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a diagram illustrating a structure of a positive electrode active material composite according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The present invention will now be described in further detail to aid in its understanding.
[0024] The terms and words used in this specification and the claims should not be interpreted limited to their ordinary and dictionary meanings, but should be interpreted in a way that is consistent with the technical idea of the present invention, based on the principle that the inventor himself / herself can appropriately define the concept of the term in order to explain the invention in the best possible way.
[0025] The terms used in the present invention are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context.
[0026] In the present invention, the terms "comprise", "include", "comprise" or "have" are intended to specify the presence of performed features, numbers, steps, components or combinations thereof, and are to be understood as not precluding the presence or possible addition of one or more other features, numbers, steps, components or combinations thereof.
[0027] The cathode active material composite of the present invention includes a cathode active material; and a coating layer formed on pores and a surface of the cathode active material; the coating layer is a coating layer formed from a coating composition including a conductive material powder and a solid electrolyte powder having a particle size (D50) of 0.3 μm to 2 μm.
[0028] The coating layer may be a dry coating layer. According to a conventional dry coating method, it is impossible to form a dry coating layer of the same quality as that of the present invention, but according to the present invention, a high-quality dry coating layer can be easily formed.
[0029] The dry coating layer does not use a solvent, so it does not require a mixing process, a heat treatment process, or a drying process, making it possible to shorten the process, and it has the effect of further reducing surface resistance because it does not generate side reactions or impurities.In addition, in the case of a wet process, phase separation occurs between the solid electrolyte and the conductive material during drying, making it difficult to form a coating layer in which the solid electrolyte and the conductive material are uniformly mixed on the surface of the active material, which also increases electrical resistance, whereas the dry coating does not have these drawbacks and provides excellent properties.
[0030] The cathode active material composite of the present invention is characterized in that the pores and surface of the cathode active material are coated with a coating composition containing a conductive material powder and a solid electrolyte powder. This coating forms a coating layer of the conductive material and solid electrolyte on the surface and inside the pores (pore walls, bottoms, internal pores, etc.) of the cathode active material, making it possible for the cathode active material to form intimate contact with the solid electrolyte and conductive material, and thus the cathode active material composite has excellent ionic conductivity and electrical conductivity.
[0031] In one embodiment of the present invention, the solid electrolyte may have a particle size (D50) of 0.2 μm to 2 μm. The solid electrolyte may have a particle size (D50) of 0.3 μm or more, 0.5 μm or more, 0.7 μm or more, 0.9 μm or more, 1.0 μm or more, or 1.2 μm or more, and may have a particle size (D50) of 1.8 μm or less, 1.6 μm or less, 1.4 μm or less, 1.2 μm or less, 1.0 μm or less, 0.8 μm or less, 0.6 μm or less, or 0.4 μm or less.
[0032] As described above, when a solid electrolyte powder having a small particle size is used, the coating on the surface of the positive electrode active material can be more uniform, and in particular, the inside of the pores in the positive electrode active material can be coated with the solid electrolyte, which can significantly improve the ionic conductivity of the positive electrode active material composite. However, if the particle size (D50) of the solid electrolyte is less than 0.2 μm, it is not preferable because the particles scatter during the dry mixing process, making the process difficult, and if it exceeds 2 μm, it is not preferable because it is difficult to insert the solid electrolyte powder into the pores of the positive electrode active material.
[0033] In one embodiment of the present invention, the positive electrode active material may include pores having a diameter of 0.5 μm to 3 μm. When the positive electrode active material includes pores in this range, the solid electrolyte powder and the conductive material powder can easily penetrate into the pores, and the pore walls, pore bottoms, etc. can be smoothly coated, which is preferable.
[0034] In one embodiment of the present invention, it is particularly preferred that the particle diameter (D50) of the solid electrolyte is smaller than the pore size of the positive electrode active material particles. Furthermore, it is more preferred that the ratio of the particle diameter (D50) of the solid electrolyte to the pore size of the positive electrode active material particles is 1:4.5 to 2:3, more preferably 1:3 to 1:2. When such conditions are satisfied, it is preferred that the solid electrolyte particles can easily penetrate into the pores of the positive electrode active material, and can smoothly coat the pore walls, pore bottoms, etc.
[0035] In one embodiment of the present invention, the positive electrode conductive material powder may be any known component in this field without limitation, and may have a particle size (D50) of, for example, 0.02 μm to 2 μm. When a fiber-shaped powder is used within the particle size range, the particle size (D50) refers to the length of the fiber powder.
[0036] In one embodiment of the present invention, the positive electrode conductive material powder preferably has a particle size that allows it to be inserted into the pores of the positive electrode active material. In this case, the particle size (D50) of the positive electrode conductive material powder can be 0.02 μm to 2 μm. The conductive material can have a particle size (D50) of 0.05 μm or more, 0.09 μm or more, 0.2 μm or more, 0.5 μm or more, 0.7 μm or more, 1.0 μm or more, or 1.2 μm or more, and can have a particle size (D50) of 1.8 μm or less, 1.4 μm or less, 1.0 μm or less, 0.6 μm or less, 0.2 μm or less, 0.1 μm or less, 0.08 μm or less, or 0.05 μm or less.
[0037] As described above, when a conductive powder having a small particle size is used, the surface of the positive active material can be more uniformly coated, and in particular, the inside of the pores in the positive active material is coated with the conductive material, so that the electronic conductivity of the positive active material composite can be significantly improved. However, when the particle size (D50) of the conductive powder is less than 0.02 μm, it is not preferable because the particles scatter during the dry mixing process, making the process difficult, and when it exceeds 2 μm, it is not preferable because it is difficult to insert the conductive powder into the pores of the positive active material.
[0038] In one embodiment of the present invention, the particle size (D50) of the conductive material powder is preferably smaller than the pore size of the positive electrode active material particles. Furthermore, it is more preferable that the ratio of the particle size (D50) of the conductive material powder to the pore size of the positive electrode active material particles is 1:20 to 1:3, more preferably 1:15 to 1:5. When such a condition is satisfied, the conductive material powder is more likely to penetrate into the pores of the positive electrode active material, and the pore walls, pore bottoms, etc. can be smoothly coated, which is preferable.
[0039] In one embodiment of the present invention, the ratio of the particle size (D50) of the conductive powder to the particle size of the solid electrolyte may be 1:200 to 1:10, and more preferably 1:160 to 1:50.
[0040] In the present invention, the particle size of the positive electrode active material, the particle size of the solid electrolyte, and the particle size of the conductive material can be measured using a Mastersizer 3000 (manufactured by Malvern), which is a wet particle size measuring device using a laser light scattering method.
[0041] The pore size of the positive electrode active material can be measured by an FE-SEM device, specifically, a JSM-7200F device (manufactured by JEOL).
[0042] In one embodiment of the present invention, the weight ratio of the conductive material to the solid electrolyte contained in the coating composition may be 0.2:9.8 to 6:4, preferably 0.7:9.3 to 3:7, and more preferably 0.8:9.2 to 1.5:8.5.
[0043] If the weight ratio of the conductive material is less than the above range, the electrical conductivity of the positive electrode active material composite may decrease, whereas if the weight ratio exceeds the above range, the electrical conductivity is improved but the contents of other components are reduced, which is undesirable.
[0044] In addition, if the weight ratio of the solid electrolyte is less than the above-mentioned range, the ionic conductivity of the positive electrode active material composite may decrease, whereas if the weight ratio exceeds the above-mentioned range, the ionic conductivity is improved but the contents of other components are undesirably reduced.
[0045] In one embodiment of the present invention, the combined weight of the conductive material and the solid electrolyte used for coating the positive electrode active material may be 2 to 50 parts by weight, preferably 3 to 20 parts by weight, and more preferably 5 to 15 parts by weight, relative to 100 parts by weight of the positive electrode active material composite.
[0046] When the combined weight of the conductive material and the solid electrolyte is less than the above-described range, the electrical conductivity and ionic conductivity of the positive electrode active material composite can be low. When it exceeds the above-described range, the electrical conductivity and ionic conductivity can be improved, but the content of the positive electrode active material decreases and the capacity of the electrode can decrease, which is not preferable.
[0047] In one embodiment of the present invention, the positive electrode active material may have a particle size (D50) of 3 μm to 30 μm. When the particle size (D50) is less than the above-described range, the coating of the solid electrolyte and the conductive material can be formed unevenly, and it is difficult for the solid electrolyte and / or the conductive material to penetrate into the pores in the active material, which is not preferable. When it exceeds the above-described range, the coating property is improved, but the active material can be cracked by friction in the secondary high-shear mixing process to induce side reactions, which is not preferable.
[0048] In one embodiment of the present invention, as the positive electrode active material, one or more selected from the group consisting of NCM, LFP, LMO, LCO, etc. can be used. Specifically, LiCoO2, LiNiO2, LiMn2O4, LiCoPO4, LiFePO4 and LiNi 1-x-y-z Co x M1 y M2 z O2 (M1 and M2 are each independently selected from the group consisting of Al, Ni, Co, Fe, Mn, V, Cr, Ti, W, Ta, Mg and Mo, and x, y and z are each independently the atomic fraction of the oxide composition element, 0 ≦ x <0.5, 0 ≦ y <0.5, 0 ≦ z <0.5, 0 <x + y + z ≦ 1), etc. Any active material particles selected from the group consisting of, or a mixture of two or more of these can be used. However, the positive electrode active material is not limited to these.
[0049] The positive electrode active material may be contained in an amount of 50 to 98% by weight based on 100 parts by weight of the positive electrode active material composite.
[0050] In one embodiment of the present invention, the solid electrolyte powder may be a powder of the solid electrolyte exemplified below. The solid electrolyte includes an ion-conductive solid electrolyte material, and may include a polymer solid electrolyte, an inorganic solid electrolyte, or a mixture of both. The solid electrolyte is preferably 10 -7 It exhibits an ionic conductivity of s / cm or higher.
[0051] In an embodiment of the present invention, the polymer solid electrolyte may be a solid polymer electrolyte formed by adding a polymer resin to a solvated lithium salt, or a polymer gel electrolyte formed by impregnating an organic electrolyte solution containing an organic solvent and a lithium salt in a polymer resin.
[0052] The solid polymer electrolyte may include, but is not limited to, one or a mixture of two or more selected from the group consisting of polyether-based polymers, polycarbonate-based polymers, acrylate-based polymers, polysiloxane-based polymers, phosphazene-based polymers, polyethylene derivatives, alkylene oxide derivatives, phosphate ester polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing an ionic dissociation group.
[0053] In a specific embodiment of the present invention, the solid polymer electrolyte may include, as a polymer resin, one or a mixture of two or more selected from the group consisting of a branched copolymer in which an amorphous polymer such as PMMA, polycarbonate, polysiloxane (pdms) and / or phosphazene is copolymerized with a comonomer on a polyethylene oxide (PEO) main chain, a comb-like polymer, and a crosslinked polymer resin.
[0054] In addition, in a specific embodiment of the present invention, the polymer gel electrolyte includes an organic electrolyte solution containing a lithium salt and a polymer resin, and the organic electrolyte solution may include 60 to 400 parts by weight based on the weight of the polymer resin. The polymer resin applied to the gel electrolyte is not limited to a specific component, and may be, for example, one or a mixture of two or more selected from the group consisting of PVC (Polyvinyl chloride), PMMA (Poly(methyl methacrylate)), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), but is not limited thereto.
[0055] In the electrolyte of the present invention, the above-mentioned lithium salt is an ionizable lithium salt, and Li + X - The anion (X) of such a lithium salt is not particularly limited, but can be represented by F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 -, CF3CO2 - , CH3CO2 - , SCN - , (CF3CF2SO2)2N - The following can be given as examples:
[0056] Meanwhile, in a specific embodiment of the present invention, the polymer-based solid electrolyte may further include an additional polymer gel electrolyte. The polymer gel electrolyte has excellent ion conductivity (or 10 -4 s / m or more) and has binding properties, so it can not only function as an electrolyte but also function as an electrode binder resin that provides binding strength between electrode active materials and between an electrode layer and a current collector.
[0057] On the other hand, in the present invention, the inorganic solid electrolyte may include a sulfide-based solid electrolyte, an oxide-based solid electrolyte, or both.
[0058] In a specific embodiment of the present invention, the sulfide-based solid electrolyte is not limited to a specific component that contains a sulfur atom among electrolyte components, and may include one or more of a crystalline solid electrolyte, a non-crystalline solid electrolyte (a glassy solid electrolyte), and a glass ceramic solid electrolyte. Specific examples of the sulfide-based solid electrolyte include an LPS-type sulfide containing sulfur and phosphorus (e.g., Li2S-P2S5), Li 4-x Ge 1-x P x S4 (x is 0.1 to 2, specifically x is 3 / 4, 2 / 3), Li 10±1 MP2X 12 (M=Ge, Si, Sn, Al, X=S, Se), Li 3.833 Sn 0.833 As 0.166 S4, Li4SnS4, Li 3.25 Ge 0.25 P 0.75 S4, Li2SP2S5, B2S3‐Li2S, xLi2S‐(100‐x)P2S5 (x is 70~80), Li2S‐SiS2‐Li3N, Li2S‐P2S5‐LiI, Li2S‐SiS2‐LiI, Li2SB2S3‐LiI, Li 10 SnP2S12 , Li 3.25 Ge 0.25 P 0.75 Examples of suitable thio-LISICON based compounds include, but are not limited to, Thio-LISICON based compounds such as S4.
[0059] In a specific embodiment of the present invention, the oxide-based solid electrolyte is an LLTO-based compound ((La, Li)TiO3), Li6La2CaTa6O 12 , Li6La2ANb2O 12 (A is Ca and / or Sr), Li2Nd3TeSbO 12 , LiBO 2.5 N 0.5 , Li9SiAlO8, LAGP-based compounds (Li 1+x Al x Ge 2-x (PO4)3, where 0≦x≦1, 0≦y≦1), LATP-based compounds such as Li2O-Al2O3-TiO2-P2O5 (Li 1+x Al x Ti 2-x (PO4))3, where 0≦x≦1, 0≦y≦1), Li 1+x Ti 2-x Al x S y (PO4) 3-y (where 0≦x≦1, 0≦y≦1), LiAl x Zr 2-x (PO4)3 (where 0≦x≦1, 0≦y≦1), LiTi x Zr 2-x (PO4)3 (where 0≦x≦1, 0≦y≦1), LPS-based compounds such as Li2S-P2S5, Li 3.833 Sn 0.833 As 0.166 S4, Li4SnS4, Li 3.25 Ge 0.25 P 0.75 S4, B2S3-Li2S, xLi2S-(100-x)P2S5 (x is 70-80), Li2S-SiS2-Li3N, Li2S-P2S5-LiI, Li2S-SiS2-LiI, Li2S-B2S3-LiI, Li3N, LISICON, LIPON-based compounds (Li 3+y PO 4-x N x, where 0≦x≦1, 0≦y≦1), Li 3.25 Ge 0.25 P 0.75 Examples of the compounds include Thio-LISICON-based compounds such as S4, perovskite-based compounds ((La, Li)TiO3), Nasicon-based compounds such as LiTi2(PO4)3, and LLZO-based compounds containing lithium, lanthanum, zirconium, and oxygen as components, and one or more of these can be included. However, the compounds are not particularly limited to these.
[0060] In one embodiment of the present invention, a sulfide-based solid electrolyte can be preferably used as the solid electrolyte.
[0061] In one embodiment of the present invention, the conductive powder is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may include one or a mixture of two or more conductive materials selected from the following: graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; graphene; carbon nanotubes; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and polyphenylene derivatives.
[0062] Hereinafter, the manufacture of a positive electrode active material composite, a positive electrode for a secondary battery including the same, and a secondary battery including the same will be described.
[0063] <Production of Positive Electrode Active Material Composite> The method may include a step of dry-mixing a positive electrode active material, a conductive material powder, and a solid electrolyte powder to prepare a mixture (primary mixing); and a step of applying a high shear force to the mixture (secondary mixing).
[0064] The primary mixing can be carried out using a blender (eg, Lab Blender, Waring) without a solvent by mixing at 4000 to 6000 rpm for 30 seconds to 5 minutes.
[0065] The secondary mixing can be carried out by applying a shear force of 100 to 250 N to the primary mixture and subjecting it to high shear mixing (eg, NOB-130, Hosokawa Micron Corporation) at 2000 to 4000 rpm for 5 to 20 minutes.
[0066] According to the above method, a positive electrode active material composite in which the conductive material powder and the solid electrolyte powder are coated on the surface and pores of the positive electrode active material can be prepared.
[0067] The cathode active material composite prepared as above may have a particle size (D50) of 3.5 μm to 40 μm, and these cathode active material composites may be used as they are, or particles having a particle size within a certain range may be selected from these and used. For example, particles having a particle size (D50) of 5 μm to 20 μm may be selected and used.
[0068] The blender and high shear mixing device used for the primary mixing and secondary mixing may be any blender or high shear mixing device known in the art without any restrictions.
[0069] <Production of positive electrodes for secondary batteries> The positive electrode for secondary battery of the present invention can be manufactured by compressing the positive electrode active material composite prepared as above into a pre-standing film, and laminating the pre-standing film on a current collector. The process of manufacturing the pre-standing film by compression can be performed using a two-roll mill MR-3 (Inoue Seisakusho Co., Ltd.).
[0070] The current collector may be any known current collector used in secondary batteries without limitation, such as stainless steel, aluminum, nickel, titanium, calcined carbon, copper, stainless steel surface-treated with carbon, nickel, titanium or silver, aluminum-cadmium alloy, non-conductive polymer surface-treated with conductive material, non-conductive polymer surface-treated with metal, conductive polymer, etc.
[0071] Specifically, the positive electrode for the secondary battery may be manufactured by pressing the positive electrode active material composite to form a pre-standing film, and laminating the pre-standing film on a current collector. The above steps may be performed by a method known in the art.
[0072] In addition, a binder may be further mixed during the preparation of the pre-standing film to prepare the pre-standing film.
[0073] In addition, when preparing the pre-standing film, a conductive material and a solid electrolyte may be further added.
[0074] Furthermore, the positive electrode for a secondary battery of the present invention can be prepared by preparing a wet coating composition from the components and coating the composition on a current collector, in addition to the method of preparing a dry pre-standing film as described above.
[0075] The pre-standing film may contain 80 to 90% by weight of the positive electrode active material composite, 0 to 10% by weight of the conductive material, and 0 to 15% by weight of the solid electrolyte, based on the total weight. Alternatively, when a binder is contained, the binder may be contained in an amount of more than 0 to 5% by weight.
[0076] In the above, the conductive material and the solid electrolyte can be the same as those described above. The binder is not particularly limited as long as it is a component that assists in bonding the positive electrode active material composite to the conductive material and the like and in bonding to the current collector. Examples of the binder include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), H-NBR, polyvinylidene fluoride polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers.
[0077] <Secondary battery manufacturing> In the present invention, the term "secondary battery" refers to all types of secondary batteries that contain the positive electrode active material composite. An example of the secondary battery is a lithium secondary battery. In particular, since the positive electrode active material composite can be suitably applied to an all-solid-state battery, the secondary battery includes an all-solid-state battery.
[0078] The manufacture of an all-solid-state battery will be described below as an example.
[0079] The all-solid-state battery includes a positive electrode, a negative electrode, and a solid electrolyte membrane interposed between the positive electrode and the negative electrode, and the positive electrode is according to the present invention and has the structural characteristics described above.
[0080] The solid electrolyte membrane may be any known solid electrolyte membrane in the art, and may be manufactured from the above-mentioned solid electrolyte. The solid electrolyte membrane may further include a known separator.
[0081] The negative electrode may include, for example, a current collector and a negative electrode active material layer formed on at least one side of the current collector. Any negative electrode known in the art may be used as the negative electrode.
[0082] Specifically, the negative electrode active material layer may include a negative electrode active material, a solid electrolyte, and a conductive material, and may further include a binder material.
[0083] The negative electrode active material may be a carbonaceous material such as natural graphite or artificial graphite (mesophase carbon microbeads (MCMB), pyrolytic carbon, mesophase pitch based carbon fiber, mesophase pitches, petroleum or coal tar pitch derived cokes, etc.); a lithium-containing titanium composite oxide (LTO), a metal (Me) which is Si, Sn, Li, Zn, Mg, Cd, Ce, Ni, or Fe; an alloy composed of the metal (Me); an oxide (MeO x and a composite of the metal (Me) with carbon; or a mixture of two or more of these may be used.
[0084] As the conductive material, solid electrolyte, and binder, those explained above can be used in the same manner.
[0085] Regarding the configuration and manufacturing method of the secondary battery of the present invention, the portions not described above may be configured and manufactured by methods known in the art without any restrictions.
[0086] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the embodiments of the present invention can be modified in various other forms, and the scope of the present invention should not be construed as being limited to the examples described below. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.
[0087] Example 1-1: Preparation of positive electrode active material composite 80g of NCM powder, which is a positive active material particle with pores having a pore diameter of 0.5μm, 9.7g of Li2S-P2S5 powder with a particle diameter (D50) of 0.4μm, and 0.3g of ECP600JD powder (Lion Corporation) with a particle diameter (D50) of 0.034μm were mixed without solvent at 5000rpm for 1 minute using a Lab Blender (Waring Corporation) (primary mixing). Next, the mixture was subjected to high shear mixing (NOB-130, Hosokawa Micron Corporation) at 3000rpm for 10 minutes with a shear force of 150N (secondary mixing) to produce a positive active material composite with a particle diameter (D50) of 6.2μm in which a coating layer was formed on the pores and surface of the positive active material.
[0088] Examples 2-1 to 6-1 and Comparative Examples 1-1 to 9-1: Preparation of Positive Electrode Active Material Composites A positive electrode active material composite was produced in the same manner as in Example 1 using the components shown in Table 1 below.
[0089] Comparative Example 10-1: Preparation of Wet Positive Electrode Active Material Composite 80g of NCM powder, which is a positive electrode active material particle with pores having a pore diameter of 0.5μm, 9g of Li2S-P2S5 powder with a particle diameter (D50) of 0.4μm, 1g of ECP600JD powder (Lion Corporation) with a particle diameter (D50) of 0.034μm, and 200ml of ethanol were mixed at 500 rpm for 20 minutes using a planetary mixer HIVIS 2P-03 (Primix Corporation). Next, the solvent was dried using a Rotary evaporator R-300 (BUCHI Corporation) to prepare a positive electrode active material composite.
[0090] [Table 1]
[0091] Examples 1-2 to 6-2 and Comparative Examples 1-2 to 10-2: Production of Positive Electrodes 90% by weight of the positive electrode active material composite prepared in Examples 1-1 to 6-1 and Comparative Examples 1-1 to 10-1, 55% by weight of Li2S-P2S, 2% by weight of carbon black powder, and 3% by weight of PTFE as a binder were mixed without solvent at 5000 rpm for 1 minute using a Lab Blender (Waring Co., Ltd.) as a blender (primary mixing). Next, a shear force of 100 N was applied to the mixture to perform high shear mixing (using PBV-0.1L, Irie Shoji Co., Ltd.) to prepare a kneaded mixture (secondary mixing). Next, the kneaded mixture was produced as a pre-standing film using a Two roll mill MR-3 (Inoue Seisakusho Co., Ltd.). Then, the pre-standing film was placed on one side of an aluminum current collector having a thickness of 15 μm and pressed to prepare the positive electrodes of Examples 1-2 to 6-2 and Comparative Examples 1-2 to 10-2, respectively.
[0092] Examples 1-3 to 6-3 and Comparative Examples 1-3 to 10-3: Production of all-solid-state batteries A lithium metal counter electrode was used, and each of the positive electrodes produced in Examples 1-2 to 6-2 and Comparative Examples 1-2 to 10-2 was used. A solid electrolyte membrane (50 μm, Li2S-P2S5) was interposed between the electrodes, and each had a capacity of 5 mAh / cm 2 Jig cells having a capacity were manufactured according to Examples 1-3 to 6-3 and Comparative Examples 1-3 to 10-3.
[0093] Test Example 1: Evaluation of initial discharge efficiency and capacity retention rate of all-solid-state batteries A driving pressure of 3 MPa was applied to each of the all-solid-state batteries manufactured in Examples 1-3 to 6-3 and Comparative Examples 1-3 to 10-3, and charging and discharging were performed twice at room temperature at 0.05C / 0.05C, and the first discharge capacity was measured as the initial discharge capacity. Then, charging and discharging were performed at 0.1C / 0.1C, and charging and discharging were performed at 0.1C / 0.5C to measure the high rate discharge capacity. The test results are shown in Table 2.
[0094] [Table 2]
[0095] From the results in Table 2, it can be seen that when the particle size (D50) of the solid electrolyte powder used in the preparation of the positive electrode active material composite is outside the range of 0.2 μm to 2 μm (Comparative Examples 1-1 and 2-1 composites), the initial discharge capacity and high rate discharge capacity of the all-solid-state batteries using the same (Comparative Examples 1-3 and 2-3) are significantly reduced. On the other hand, when the particle size (D50) of the solid electrolyte powder used in the preparation of the positive electrode active material composite is within the above range (Examples 1-1 to 6-1 composites), it can be confirmed that the initial discharge capacity and high rate discharge capacity of the all-solid-state batteries using the same (Examples 1-3 to 6-3) are significantly improved.
[0096] Meanwhile, when the weight ratio of the conductive material to the solid electrolyte used for coating the active material during the preparation of the positive electrode active material composite is in the range of 0.2:9.8 to 6:4 (composites of Examples 1-1 to 6-1), it can be confirmed that the initial discharge capacity and high rate discharge capacity of the all-solid-state battery using the same (composites of Examples 1-3 to 6-3) are significantly improved. On the other hand, when the weight ratio of the conductive material to the solid electrolyte is out of the range (composites of Comparative Examples 3-1 to 6-1), it can be confirmed that the initial discharge capacity and high rate discharge capacity of the all-solid-state battery using the same (composites of Comparative Examples 3-3 to 6-3) are significantly decreased.
[0097] In addition, when the combined weight of the conductive material and solid electrolyte used in coating the active material is within the range of 2 to 50 parts by weight relative to 100 parts by weight of the positive electrode active material composite (composite of Examples 1-1 to 6-1), it can be confirmed that the initial discharge capacity and high rate discharge capacity of the all-solid-state battery using this (composite of Examples 1-3 to 6-3) are significantly improved. On the other hand, when the combined weight of the conductive material and solid electrolyte used in coating the active material is outside this range (composite of Comparative Examples 7-1 to 8-1), it can be confirmed that the initial discharge capacity and high rate discharge capacity of the all-solid-state battery using this (composite of Comparative Examples 7-3 to 8-3) are significantly decreased.
[0098] In addition, it was confirmed that the initial discharge capacity and high rate discharge capacity of the all-solid-state battery (Comparative Example 10-3) manufactured using the cathode active material composite manufactured by wet coating (Comparative Example 10-1) were significantly reduced compared to the cathode active material manufactured by dry coating. This result is believed to be due to the fact that phase separation occurs between the solid electrolyte and the conductive material during wet coating, making it impossible to form a coating layer in which the solid electrolyte and the conductive material are uniformly mixed on the surface of the active material.
Claims
1. A positive electrode active material, and A positive electrode active material composite including pores of the positive electrode active material and a coating layer formed on a surface thereof, The coating layer is formed from a coating composition including a conductive material powder and a solid electrolyte powder having a particle size (D50) of 0.3 μm to 2 μm, The coating layer is a dry coating layer, The particle size (D50) of the conductive powder is 0.02 μm to 0.6 μm, The weight ratio of the conductive material to the solid electrolyte contained in the coating composition is 0.2:9.8 to 6:4; A cathode active material composite, wherein the combined weight of the conductive material and the solid electrolyte used for coating the cathode active material is 2 to 50 parts by weight per 100 parts by weight of the cathode active material composite.
2. 2. The positive electrode active material composite according to claim 1, wherein the positive electrode active material contains pores having a diameter of 0.5 μm to 3 μm.
3. The positive electrode active material is LiCoO 2 , LiNiO 2 , LiMn 2 O 4 , LiCoPO 4 , LiFePO 4 , and LiNi 1-x-y-z Co x M1 y M2 z O 2 (M1 and M2 are each independently any one selected from the group consisting of Al, Ni, Co, Fe, Mn, V, Cr, Ti, W, Ta, Mg, and Mo, and x, y, and z are each independently any one or more selected from the group consisting of 0≦x<0.5, 0≦y<0.5, 0≦z<0.5, and 0<x+y+z≦1 as atomic fractions of oxide composition elements).
4. 2. The cathode active material composite according to claim 1, wherein the solid electrolyte powder is a sulfide-based solid electrolyte powder.
5. A positive electrode for a secondary battery comprising the positive electrode active material composite according to claim 1 .
6. The positive electrode for a secondary battery according to claim 5 , further comprising a conductive material and a solid electrolyte.
7. The positive electrode for a secondary battery according to claim 6 , further comprising a binder.
8. A secondary battery comprising the positive electrode for secondary batteries according to claim 5, a negative electrode, and a solid electrolyte.
Citation Information
Patent Citations
Lithium secondary battery
JP2002373643A
Lithium secondary battery and its manufacturing method
JP2003059492A
Positive-electrode active material for lithium secondary battery and its manufacturing method, and positive electrode for lithium secondary battery active material and lithium secondary battery using positive electrode
JP2009117241A
Manufacturing method of all solid-state battery, manufacturing method of electrode, and manufacturing method of electronic device
JP2016189339A
Positive electrode for rechargeable lithium battery and rechargeable lithium battery including the same
KR1020150064697A